2019
DOI: 10.1101/709519
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Auditory Activity is Diverse and Widespread Throughout the Central Brain ofDrosophila

Abstract: Sensory pathways are typically studied by starting at receptor neurons and following postsynaptic neurons into the brain. However, this leads to a bias in analysis of sensory activity towards the earliest layers of sensory processing or to brain regions containing the majority of postsynaptic neurons. Here, we present new methods for unbiased volumetric neural imaging with precise across-brain registration, to characterize auditory activity throughout the entire central brain of Drosophila, and to make compari… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 68 publications
(80 reference statements)
2
40
0
Order By: Relevance
“…5 and 6). We used pan-neuronal imaging with registration to map responses that continue following pC1 optogenetic activation (previously this technique had only been used to map sensory activity (Pacheco et al, 2019) and spontaneous activity (Mann et al, 2017)). We found that activation of pC1-Alpha neurons drives robust persistent neural activity throughout the posterior dorsal regions of the central brain (known to contain the processes of sexually dimorphic neurons (Cachero et al, 2010;Kimura et al, 2015)), lasting for minutes following activation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5 and 6). We used pan-neuronal imaging with registration to map responses that continue following pC1 optogenetic activation (previously this technique had only been used to map sensory activity (Pacheco et al, 2019) and spontaneous activity (Mann et al, 2017)). We found that activation of pC1-Alpha neurons drives robust persistent neural activity throughout the posterior dorsal regions of the central brain (known to contain the processes of sexually dimorphic neurons (Cachero et al, 2010;Kimura et al, 2015)), lasting for minutes following activation.…”
Section: Discussionmentioning
confidence: 99%
“…5A). To compare activity across flies and to map activity onto a reference atlas, we used a recently developed pipeline for two-photon volumetric calcium imaging, motion correction, registration, and region of interest (ROI) segmentation (Pacheco et al, 2019), and scanned the entirety (in the z dimension) of a dorsal portion of a single brain hemisphere in each fly ( Fig. 5A).…”
Section: Activation Of Pc1-alpha Neurons Drives Persistent Neural Actmentioning
confidence: 99%
See 2 more Smart Citations
“…The perception of wind is crucial for animal navigation, particularly for flying animals and for anemotaxis. The LH receives projections from a third-order mechanosensory region of the brain known as the wedge [5,15,[66][67][68] (Figure S6A). Activating a line labelling WED-PN1 (R37E08) can generate increased wing-flick motion and differential wingangling [69] ( Figure S6C).…”
Section: Mechanosensory-olfactory Integration Occurs In the Lateral Hornmentioning
confidence: 99%